Fiduciary Dispute Settlement of Murabaha Contract in PT. Al-Ijarah Indonesia Finance - Riska Wijayanti; Kartika Marella Vanni (Journal of Islamic Economic Laws, 2019)
This study examines the authority of dispute settlement body of a bad financing in murabaha contracts with a collateral of Daihatsu VVTI car 13 XI DLX Year 2011 midnight black color. According to DSN Fatwa Number 04/DSN-MUI/IV/2000 concerning Murabaha the placement of fiduciary on murabaha contract objects is indeed permissible, but it becomes ambiguous when murabaha objects which are used as collateral in the financing process that have not been repaid are lost, causing late installment payments. The customer argued that the late payment was due to the embezzlement of murabaha objects by third parties beyond the expectations or control of the customer. This study also examines the legal liability for late settlement of murabaha sale and purchase by customers due to the loss of murabaha objects which at the same time become collateral in murabaha financing contracts. This research is normative legal research with a legal approach and a case approach. This study concludes that Religious Courts have the authority to decide disputes that occur between customers (mushtari) and sharia financial institutions (ṣahib al-māl) for late repayment of murabaha financing. Based on the principle of accountability based on the element of error, the customer (mushtari) has legal responsibility for his actions. Errors made by customers (mushtari) are in the form of negligence.